Les nouvelles voies du comparatisme - Roland, Hubert (Cahier voor Literatuurwetenschap, 2010)
Which recent methodological innovations have occurred in the field of comparative literature? What are the critical paradigms behind the practices of comparative research today? These questions are the starting point of the present issue which brings together different comparative studies from the vantage points of: methodological and epistemological reflection about (in)comparability and difference; transversal phenomena of acculturation, networks and intercultural dialogues; the hybridity of (natural and conceptual) languages, translation and transposition. In this way, the studies presented in this volume hope to foster discussions about the foundation, the history, the limits and the methods of comparatives studies today.